Ag/Ag2S Nanocrystals for High Sensitivity Near‐Infrared Luminescence Nanothermometry. (28th December 2016) - Ruiz, Diego; del Rosal, Blanca; Acebrón, María; Palencia, Cristina; Sun, Chen; Cabanillas‐González, Juan; López‐Haro, Miguel; Hungría, Ana B.; Jaque, Daniel; Juarez, Beatriz H.
Abstract : Temperature sensing in biological media (cells, tissues, and living organisms) has become essential in the development of the last generation of diagnostics and therapeutic strategies. Thermometry can be used for early detection of different diseases, such as cancer, stroke, or inflammation processes, one of whose incipient symptoms is the appearance of localized temperature singularities. Luminescence nanothermometry, as a tool to accurately provide temperature sensing in biological media, requires the rational design and development of nanothermometers operating in the second biological window. In this work, this is achieved using Ag/Ag2 S nanocrystals as multiparametric thermal sensing probes. Temperature sensing with remarkably high sensitivity (4% °C −1 ) is possible through intensity‐based measurements, as their infrared emission is strongly quenched by small temperature variations within the biological range (15–50 °C). Heating also results in a remarkable redshift of the emission band, which allows for concentration‐independent temperature sensing based on infrared ratiometric measurements, with thermal sensitivity close to 2% °C −1 . These results make Ag/Ag2 S nanocrystals the most sensitive among all noncomposite nanothermometers operating in the second biological window reported so far, allowing for deep‐tissue temperature measurements with low uncertainty (0.2 °C). Abstract : The outstanding infrared fluorescence thermal sensing capabilities of Ag2 S nanocrystals are reported . Ag2 S nanocrystals are here introduced to the scientific community as thermal nanoprobes capable of real‐time subcutaneous contactless temperature sensing with a subdegree resolution. In combination with their long‐term stability and low toxicity, their thermal sensing capabilities make Ag2 S nanocrystals unique bioprobes.